Communication Analysis in Bullying Prevention in Islamic Boarding Schools in Pasuruan Regency - Muhammad Syaifuddin; Zainul Ahwan (Communicator: Journal of Communication, 2024)
This study aims to analyze the communication between students and administrators of Annur Assalafy Islamic Boarding School in an effort to prevent bullying. This study uses a descriptive qualitative approach with a phenomenological method and relies on interviews and documentation as data collection techniques. Data analysis was carried out through the process of collecting, reducing, presenting data, and drawing conclusions. The results of the study showed that there was one-way and two-way communication, with interactions such as ngaji, jagongan, and mayoran reflecting horizontal and two-way communication. Vertical communication between administrators and students and horizontal communication between students complement each other in creating a safe and supportive Islamic boarding school environment. This communication is effective in reducing bullying cases and strengthening solidarity between students. Personality factors were found to be the main cause of bullying.